Isolation and Identification of Bacteria Associated with Lubricant Oil Contaminated Soil - Galadima, Musa (International Journal of Pharmaceutical & Biological Archive, 2021)
Environmental pollution with petroleum and petroleum products has been recognized as one of the significant causes of environmental pollution, and in concert to reduce these effects, bacterial organisms are known to adapt to these condition which could serve as potential bioremediators. Isolation and identification of bacteria associated with lubricant oil contaminated soil were carried out using two mechanic workshops and gasoline stations in Kebbi state, Nigeria. Ten grams of the sample soil were taken from each workshop and cultured using the conventional bacteriological isolation and identification technique. The bacterial organisms identified WERE Staphylococcus aureus, Pseudomonas spp., Micrococcus spp. Lactobacillus fermentum, Proteus vulgaris, and Salmonella spp. S. aureus was the dominant species having highest percentage prevalence 23.80%. Pseudomonas spp. had a prevalence of 19.04% while the organisms with the least percentage occurrence were L. fermentum, Salmonella spp., and P. vulgaris with 4.76% prevalence. This study examined the ubiquity of S. aureus showing ITS ability to adapt to conditions present in soil contaminated with lubricant oil.